RANCANG BANGUN PROTOTYPE PENJEMUR PAKAIAN OTOMATIS BERBASIS MIKROKONTROLER ATMEGA8535 - Eko Rismawan; Sri Ratna Sulistiyanti; Agus Trisanto (Jurnal Informatika dan Teknik Elektro Terapan (JITET), 2013)
Abstract Currently the application of sensors to facilitate human work is increasing. One is the use of rain sensors applied in clothes horse. Microcontroller will receive the signal from the sensor, and gave the command to the motor driver for DC motor command rotates left or right. DC motor rotation direction is determined by the direct orders of the Microcontroller. Microcontroller as the brain to rule, so in order not to rely on any of the DC motor running. Clothesline able to move as far as approximately 1.5 meters. The goal is to roll the rail motors clothesline, clothesline or clothes that do not become wet because of the rain. Once the clothes horse entered the microcontroller will tell the blower to live.Keywords : Rain Sensor, Motor Drivers, DC Motor